Antimicrobial Stewardship Programs: Comparison of a Program with Infectious Diseases Pharmacist Support to a Program with a Geographic Pharmacist Staffing Model. Issue 6 (June 2015) - Bessesen, Mary T.; Ma, Andrew; Clegg, Daniel; Fugit, Randolph V.; Pepe, Anthony; Goetz, Matthew Bidwell; Graber, Christopher J.
Background: Stewardship of antimicrobial agents is an essential function of hospital pharmacies. The ideal pharmacist staffing model for antimicrobial stewardship programs is not known. Objective: To inform staffing decisions for antimicrobial stewardship teams, we aimed to compare an antimicrobial stewardship program with a dedicated Infectious Diseases (ID) pharmacist (Dedicated ID Pharmacist Hospital) to a program relying on ward pharmacists for stewardship activities (Geographic Model Hospital). Methods: We reviewed a randomly selected sample of 290 cases of inpatient parenteral antibiotic use. The electronic medical record was reviewed for compliance with indicators of appropriate antimicrobial stewardship. Results: At the hospital staffed by a dedicated ID pharmacist, 96.8% of patients received initial antimicrobial therapy that adhered to local treatment guidelines compared to 87% of patients at the hospital that assigned antimicrobial stewardship duties to ward pharmacists ( P < .002). Therapy was modified within 24 hours of availability of laboratory data in 86.7% of cases at the Dedicated ID Pharmacist Hospital versus 72.6% of cases at the Geographic Model Hospital ( P < .03). When a patient's illness was determined not to be caused by a bacterial infection, antibiotics were discontinued in 78.0% of cases at the Dedicated ID Pharmacist Hospital and in 33.3% of cases at the Geographic Model Hospital ( P < .0002). Conclusion: An antimicrobial stewardship program with a dedicated ID pharmacist was associated with greater adherence to recommended antimicrobial therapy practices when compared to a stewardship program that relied on ward pharmacists.